Blood Myeloid Dendritic Cells and slanDC in Antiretroviral Therapy- Suppressed HIV-Infected Patients - Lichtner, Miriam; Rossi, Raffaella; Vita, Serena; Savinelli, Stefano; Iannetta, Marco; Mascia, Claudia; Marocco, Raffaella; Ajassa, Camilla; Mengoni, Fabio; Scorzolini, Laura; Maria Mastroianni, Claudio; Vullo, Vincenzo (Current HIV Research, 2016)
Myeloid dendritic cells (mDCs) play a complex role in HIV infection regardless of viral replication. The aim of our study was to analyse mDCs in long term antiretroviral therapy (ART)- suppressed HIV-infected patients. We evaluated the numbers of mDCs and slanDC in the context of different degree of CD4+ T cell recovery, persistent T cell activation (as HLA-DR+/CD38+ expression) and monocyte-macrophage activation assessed in terms of circulating levels of both sCD14 and sCD163. We enrolled 72 aviremic patients under effective ART and 34 healthy donors (HD). Patients were divided into two groups on the bases of ΔCD4, indicating the difference between the value of CD4 at the time of sampling and CD4 nadir. Higher levels of mDCs and slanDC were found in patients with ΔCD4>200/mmc in comparison to HD. In those patients also an increased level of sCD14 was found, whereas sCD163 seemed to be at normal levels. An augmentation of activated CD4 T lymphocytes was found, although less pronounced in patients with ΔCD4<200/mmc. In conclusion, our findings showed an expansion of mDCs with a shift to inflammatory slanDC that could sustain both microbial translocation and HIV latency in CD4 T cells.
Keywords: ART